2016
DOI: 10.1111/apm.12577
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of enteroaggregative Escherichia coli isolates from pediatric population in Pakistan

Abstract: Enteroaggregative Escherichia coli (EAEC) are a leading cause of diarrhea among children. The objective of this study was to define the frequency of EAEC among diarrheal children from flood-affected areas as well as sporadic cases, determine multidrug resistance, and evaluation of virulence using an in vivo model of pathogenesis. Stool samples were collected from 225 diarrheal children from 2010 to 2011 from flood-affected areas as well as from sporadic cases in Pakistan. Identified EAEC isolates were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…The high AMR frequencies for first-line drugs, in particular penicillins, detected in this study are similar to reports of other intestinal, extra-intestinal and environmental isolates of E. coli 22,37 . Of note, the high levels of ciprofloxacin-resistance found in this study at the Asian sites corresponded to high levels reported in clinical cases in India, Bangladesh and Pakistan 17,18,21,23,24,38 . Further, while ESBL-producing aEPEC were detected in this study in Asia, the frequency of these was lower than those reported from hospitals in both Asia and Africa 18,21,31,38 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The high AMR frequencies for first-line drugs, in particular penicillins, detected in this study are similar to reports of other intestinal, extra-intestinal and environmental isolates of E. coli 22,37 . Of note, the high levels of ciprofloxacin-resistance found in this study at the Asian sites corresponded to high levels reported in clinical cases in India, Bangladesh and Pakistan 17,18,21,23,24,38 . Further, while ESBL-producing aEPEC were detected in this study in Asia, the frequency of these was lower than those reported from hospitals in both Asia and Africa 18,21,31,38 .…”
Section: Discussionsupporting
confidence: 83%
“…While limited AMR data for E. coli are available from the seven countries where the GEMS sites were located, there are no national surveillance data from any of these countries. Furthermore, AMR data on E. coli in these countries predominately pertain to E. coli causing extra-intestinal infections and to a limited number of drugs, mainly third-generation cephalosporins and fluoroquinolones 21,[23][24][25]31 . Here we present the first comprehensive AMR phenotypic data and molecular characterization for multiple antimicrobials, detecting several common mobile elements mediating the AMR including small plasmids, class I integrons with different cassettes and transposons including Tn6029, Tn10 and Tn1721 ( Fig S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ethical reasons, studies with human volunteers that would best reproduce bacterial virulence is not currently feasible (Nataro et al, 1995), therefore, studies make use of animal models, mainly rodents, as a way to investigate aspects of the EAEC pathogenesis and, in recent years, for ethical and costs reasons, the use of invertebrate models has been implemented for studies of several microorganisms, even for EAEC (Morin et al, 2010; Roche et al, 2010; França et al, 2013; Jønsson et al, 2016; Khalil et al, 2016). In this context, the larvae of Galleria mellonella (Lepidoptera: Pyralidae) shows several morphological, physiological and immunological advantages over other invertebrate models (Tsai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the hemocyte-mediated cellular immune response, G. mellonella also has a humoral immune response consisting of effector molecules, including opsonins (Park et al, 2005; Shaik and Sehnal, 2009), antimicrobial peptides (Lee et al, 2004; Brown et al, 2009), and melanin (Soderhall and Cerenius, 1998). Previously, Jønsson et al (2016) and Khalil et al (2016) analyzed only typical EAEC strains in this same model, comparing it with non-pathogenic E. coli and validating the model for EAEC pathogenicity studies.…”
Section: Introductionmentioning
confidence: 99%